1984
DOI: 10.1099/00221287-130-6-1557
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of (l->3)- - and (l->4)- -Glucan Synthases Along the Hyphae of Saprolegnia monoica

Abstract: Protoplasts from hyphae of Saprolegnia monoica, collected from lytic medium after different times of incubation, represented a sequential fractionation of mycelium from apical to distal zones. This method gives the opportunity to study the intrahyphal localization of cell wall glucan synthases in relation to apical growth. (1 +4)-P-Glucan synthases were mainly found in early protoplasts (i.e. from apical zones) while the highest (1 +3)+glucan synthase activities were recovered in late protoplasts (i.e. from th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

1985
1985
2003
2003

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 16 publications
1
4
0
Order By: Relevance
“…Also, in the cytosol of fungal hyphae, the Ca 2+ concentration is known to be higher at the elongating apex than in the nongrowing parts of the hyphae (63,64). From these observations, and in agreement with the data of Girard and Fe `vre (65), it has been proposed that the enzyme working at pH 9 would be more specifically located in the growing apical part of the hyphae, whereas the enzyme with a pH optimum of 6 would have a subapical localization (46). This hypothesis is in keeping with a recent report that shows that (1f3)-β-D-glucans are present in all regions of both elongating and nonelongating hyphae of the Oomycete Achlya bisexualis, a close relative of S. monoı ¨ca (66).…”
Section: Discussionsupporting
confidence: 87%
“…Also, in the cytosol of fungal hyphae, the Ca 2+ concentration is known to be higher at the elongating apex than in the nongrowing parts of the hyphae (63,64). From these observations, and in agreement with the data of Girard and Fe `vre (65), it has been proposed that the enzyme working at pH 9 would be more specifically located in the growing apical part of the hyphae, whereas the enzyme with a pH optimum of 6 would have a subapical localization (46). This hypothesis is in keeping with a recent report that shows that (1f3)-β-D-glucans are present in all regions of both elongating and nonelongating hyphae of the Oomycete Achlya bisexualis, a close relative of S. monoı ¨ca (66).…”
Section: Discussionsupporting
confidence: 87%
“…Its activity was higher in protoplasts released after 45 min than in protoplasts collected after 90 min lysis, suggesting that the enzyme may be located in the apical part of the hypha. This contrasts strongly with the Ca 2+ , Mn 2+ and Mg 2+ inhibition of the former characterized enzyme and with its subapical localization (Girard & Fèvre, 1984). A concentration gradient of free Ca 2+ occurs in the cytosol of growing hyphae with the concentration of the divalent cation highest at the apex (Jackson & Heath, 1993; Levina et al , 1995).…”
Section: Discussionmentioning
confidence: 74%
“…It is therefore possible that l,3- β -GSl and l,3- β -GS2 are found at different sites in the hypha since the previously described glucan synthase (i.e. l,3- β -GSl) was found associated with subapical cytoplasm (Girard & Fevre, 1984).…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Studies of the Oomycete Saprolegnia monoica have shown ␤-1,3-glucan synthase activity is highest near the hyphal apex (Girard and Fè vre, 1984). Interestingly the activity of ␤-1,4-glucan synthase is highest in a subapical zone, suggesting that cellulose microfibril deposition is not concentrated within the apical dome.…”
Section: Fungal Cell Structure and Functionmentioning
confidence: 97%